FORMATION OF PROFESSIONAL COMPETENCES OF FUTURE MOTOR VEHICLE PROFILE SPECIALISTS WITH THE USE OF TECHNOLOGIES OF DISTANCE LEARNING INTERACTION - Kuchma Oleksandr; Filatov Sergiy (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2022)
The article emphasizes the need to update the content of professional training of specialists for the transport industry in connection with radical changes in the Ukrainian economy and the revision of educational and professional standards. The aims of the article are to determine the content and essence of professional competences of future motor vehicle profile specialists, as well as the principles and approaches that contribute to its formation in the conditions of distance learning interaction. In order to reveal the main directions of the formation of professional competences of future motor vehicle profile specialists, a set of methods has been used, including analysis, generalization and modelling of the content of professional competencies, study and research of advanced pedagogical experience in the application of technologies of distance learning interaction. It has been found that the professional competence of future motor vehicle profile specialists is an integrative dynamic personality characteristic based on a set of special knowledge, practical skills, skills in the field of transport and information technologies, their personal qualities, which ensures their performance of professional responsibilities at a productive level. The content of professional competence is an invariant set of essential professional competences related to the realisation of management functions in motor vehicle enterprises and the performance of typical professional tasks to operate, repair, and maintain vehicles. It has been established that the professional competence of a specialist in the motor transport industry is a multidimensional phenomenon which can be characterized by scientific research, organizational management, project design, production technology, and service-operational competence. Professional competence provides the specialist with the realization of motivational and promotional, gnostic, practical and operational, communicative, control and evaluation functions in professional activity. The analysis of modern distance learning tools showed their significant potential in updating the content, forms and methods of organizing the students’ professional training for the motor vehicle area of expertise. It has been revealed that the formation of professional competence of appointed specialists in the conditions of distance and mixed learning can be carried out in such forms of educational activity as academic, quasi-professional, educational-professional and extracurricular independent studies. The possibilities of electronic educational complexes, online lectures and frontal laboratory and practical classes, virtual and with augmented reality simulators, study SMART systems, electronic communicators, learning content management systems, open electronic educational resources, and MOOC in the formation of components of students’ professional competence have been described. It has been substantiated that the construction of distance learning interaction based on the principles of systematicity, interdisciplinarity, professional focus, interactivity, keeping a record of the regional characteristics, and gamification, as well as application of the regulations of competency-based, activity-oriented and personal-focused approaches will contribute to the training of future highly qualified motor vehicle profile specialists.